Website training - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
training programme on Website design, CTA organised five workshops during the second half of 1998. The workshops were held in Senegal, Tanzania, Trinidad and Tobago, and Botswana